(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online food delivery services have dramatically expanded in recent years. Recently, the majority of businesses have started providing REL-passengers with wholesome meals. Before, there was no other choice for train travelers. REL-food was one of the cutting-edge applications that offered food services to train travelers in the most recent year. The study’s main goal is to determine customer satisfaction with the online meal service provided by REL- food and to offer recommendations for improving customer service.